2009
DOI: 10.3797/scipharm.0905-07
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 7-chloroquinolinyl-4-

Abstract: amino]chalcone derivatives derived from the corresponding 3-or 4-[(7-chloroquinolin-4-yl)amino]acetophenone were synthesized and evaluated for in vitro antimalarial and anticancer activity. The most active compounds 12, 13, 15, 17 and 19 from the 3-substituted series displayed inhibitory values against heme cristallization in the range of 93.14 ± 1.74 -94.93 ± 1.50 % as an antimalarial mechanism and cytotoxic effect with IC 50 values of 7.93 ± 2.05, 7.11 ± 2.06 and 6.95 ± 1.62 µg/mL for 13, 17 and 19 respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…11) possess antimalarial and anticancer activities. These hybrids showed 93-95% inhibition of β-hematin synthesis which is comparable to CQ (Ferrer et al, 2009). Since these CQ-chalcone hybrids also possess anticancer activity, it would be interesting to examine anticancer profile of other CQ-chalcone hybrids with antimalarial activity.…”
Section: Learning From the Cq Hybrid Approach For Antimalarial Drug Dmentioning
confidence: 70%
See 1 more Smart Citation
“…11) possess antimalarial and anticancer activities. These hybrids showed 93-95% inhibition of β-hematin synthesis which is comparable to CQ (Ferrer et al, 2009). Since these CQ-chalcone hybrids also possess anticancer activity, it would be interesting to examine anticancer profile of other CQ-chalcone hybrids with antimalarial activity.…”
Section: Learning From the Cq Hybrid Approach For Antimalarial Drug Dmentioning
confidence: 70%
“…11) against human prostate cancer cells (LNCaP) demonstrated good cytotoxic effects (IC 50 : 6.0-8.0 mg/ml). However, further elaboration of this study is needed to unravel the mode of action and SAR effects (Ferrer et al, 2009). Engen et al (2010) reported merged hybrids of aryl heteroaryl urea (AHU) using 4-aminoquinoline scaffold as one part of the hybrid and studied them against insulin-like growth factor receptor (IGF-1R).…”
Section: Miscellaneous Hybrids Of Cq/4-aminoquinolinementioning
confidence: 98%
“…1H NMR (270 MHz, CDCl 3 ): δ = 2.49 (s, 3H, CH 3 ), 3.83 (s, 3H, OCH 3 ), 3.89 (s, 2H, CH 2 ), 6.86 (dd, 1H, H3′, J 1 = 1. 24 15.5, 35.5, 55.9, 110.2, 119.9, 120.2, 120.5, 121.3, 124.5, 124.8, 125.1, 125.3, 126.9, 127.3, 129.1, 141.9, 142.4, 147.9, 152.6, 165.7, 168.4 ,57.95;H,3.98;N,9.22;found: C,58.01;H,4.03;N, 15.5,35.1,55.4,105.9,110.7,112.2,120.9,124.9,125.3,127.6,128.9,129.7,129.8,137.4,138.6,146.5,147.4,148.9,152.7,153.3,160.3,166.5. Anal.…”
Section: General Technique For the Synthesis Of 2-[2-(7-chloroquinolimentioning
confidence: 99%
“…[12][13][14][15][16][17] A further approach refers to a superimposition in a single molecular scaffold of the structural features responsible for the activity of different antimalarial and anticancer agents. [18][19][20][21][22][23] In our previous reports, [24][25][26][27] different quinoline compounds were designed and synthesized. The in vitro and in vivo biological activities of these compounds showed promising potential as antimalarial and anticancer compounds.…”
Section: Introductionmentioning
confidence: 99%
“…general interest in the preparation of heterocyclic compounds with potential anticancer activities [18][19][20][21][22][23], herein we report the synthesis of indeno [1,2-b]indole derivatives, and their characterization by X-ray diffraction analysis. Docking simulation was performed using X-ray crystallographic structure of MMP-9 in complex with the most active inhibitor to explore the binding mode of the compound at the active site.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%